The Relationship Between Government Regulation and Competition - Charles Cutler (Washington University Law Quarterly, 1977)
There has been, and is, a battle of remarkable proportions being waged in the field of computer-related communications. Essentially, the protagonists are: the telephone industry, new “specialized” communications common carriers, independent equipment manufacturers, and major users of communications. In this Article, Charles R. Cutler discusses the effects of certain substantive regulations on both industries and considers whether regulations should be promulgated at the federal or state level. He concludes that the stakes are high and the contest for dominance between the computer and communications industries is not yet over.
Keywords: Rate regulation; Telephones